The role of kisspeptin system in cancer biology. (October 2019) - Stathaki, Martha; Stamatiou, Maria Evanthia; Magioris, George; Simantiris, Spyridon; Syrigos, Nikolaos; Dourakis, Spyridon; Koutsilieris, Michael; Armakolas, Athanasios
Graphical abstract: Highlights: The antimetastatic effect of Kisspeptins is generated through phosporylation of different MAPK'S and dephosphorylation of Akt. Activation of intracellular kinases upon kisspeptin stimulation appears to be, at least partially, dependent on the cellular context. In breast and ovarian cancer kisspeptin expression has been associated with metastasis and tumor growth. In breast cancer the KiSS-1/KiSS-1R signaling may be able to regulate the initiation, progression, proliferation and metastasis of breast cancer cells through the activation of RhoA GTPases and by inducing an increase in MMP-9 activity. In triple-negative breast cancer, there is KiSS-1 and KiSS-1R upregulation and KiSS-1R signaling promotes drug resistance and tumor invasion. Abstract: Kisspeptins are a family of neuropeptides that are known to be critical in puberty initiation and ovulation. Apart from that kisspeptin derived peptides (KPs) are also known for their antimetastatic activities in several malignancies. Herein we report recent evidence of the role of kisspeptins in cancer biology and we examine the prospective of targeting the kisspeptin pathways leading to a better prognosis in patients with malignant diseases.